Evaluation of physicochemical, phytochemical, antioxidant and carotenoid properties of watermelon Citrullus lanatus juice at different storage temperatures and treatments / Nur Shafinaz Mohamad Salin - Mohamad Salin, Nur Shafinaz (2022)
Watermelon (Citrullus lanatus) is a perishable fruit with significant phytochemicals, carotenoids and antioxidant properties that are beneficial to human health. Due to convenience, majority of the individuals prefer to consume watermelon in juice form. In this study, watermelon juice was treated and stored at room temperature (25°C), refrigerator cold (4°C), refrigerator freeze (-8°C) and freeze-dried, and were analyzed on day 1, day 3, day 5, day 7 and day 9 on the juice physicochemical, phytochemical, antioxidant and carotenoid quantification.